A comparative analysis of caries and fluorosis among cities with and without public water supply fluoridation in São Paulo State, Brazil - Moimaz, Suzely Adas Saliba [UNESP] (2010)
Purpose: This population-based, cross-sectional study aimed to record the DMFT index for 12 year-old children with dental caries and fluorosis levels in cities with and without public water supply fluoridation. Methods: From the 101 municipalities belonging to the Health Regional Department XV (DRSXV-SJRP) of the São Paulo state in the Southeast region of Brazil, 85 cities were selected after exclusion of those with incomplete data and less than ten years of fluoridation treatment in 2004. The criteria adopted for the assessment of dental caries and fluorosis levels were based on the guidelines published in the WHO Manual 4th edition. The data were analyzed using Fisher’s exact tests at a significance level of 5%. Results: The prevalence of caries in 12 year-old children had no significant association with fluoridated water, and was considered “moderate” and “high” in cities without fluoridation and “low” and “moderate” in cities with fluoridation. A significant association was found between water fluoridation and fluorosis (P=0.001), but not between water fluoridation and the DMFT index (P=0.119). Conclusion: The prevalence of fluorosis was related to water fluoridation in this study. However, fluorosis was also observed in non-fluoridated cities, which may result from fluoride intake through other sources.